How to drag with a worn-out mouse? Searching for social justice through collaboration - Penteado, Miriam Godoy [UNESP]; Skovsmose, Ole (Springer Nature, 2009)
We consider what a concern for social justice in terms of social inclusion might mean for teacher education, both practising and prospective, with particular reference to the use of information and communication technology (ICT) in mathematics education taking place at a borderland school. Our discussion proceeds through the following steps: (1) We explore what a borderland position might denote to address what social inclusion might mean. (2) We consider the significance of mathematics education and the use of ICT for processes of social inclusion. (3) We briefly refer to the Interlink Network, as many of our observations emerge as reflections on this project. (4) We present different issues that will be of particular importance with respect to teacher education if we want to establish a mathematics education for social inclusion. These issues concern moving away from the comfort zone, establishing networks, identifying new approaches, moving beyond prototypical research, and getting in contact. This brings us to (5) final considerations, where we return to the notion of social justice. © Springer Science+Business Media B.V. 2009.
Keywords: Borderland school; Computers and mathematics education; Risk zone; Social inclusion; Teacher-researcher collaboration